Comparative Potentiometric Study Using Modified 2-Hydroxypropyl b-Cyclodextrin and Modified Carbon Nanotubes Sensors for Determination of Ambroxol Hydrochloride - A. Alarfaj1, Nawal; F. El-Tohamy2, Maha (Asian Journal of Chemistry, 2014)
A novel and sensitive electrochemical method for potentiometric determination of ambroxol hydrochloride was proposed. The proposed method was based on the fabrication of four ambroxol sensors using o-nitrophenyloctyl ether as plasticizer in a polymeric matrix polyvinyl chloride. Sensors I and II were conventional plastic membrane type and prepared from ambroxol-phosphomolybdate as ion pair, while sensor II was modified using 2-hydroxypropyl b-cyclodextrin as an ionophore. Sensors III and IV were carbon paste type and fabricated using ambroxol-phosphotungstate as ion pair while, sensor IV was modified using carbon nanotubes. The fabricated sensors were carefully investigated and characterized. They displayed Nernstian responses of (54.50 ± 0.6, 56.29 ± 0.3, 57.95 ± 0.8 and 58.32 ± 0.2 mV decade-1) for sensors I, II, III and IV, respectively at 25 °C over drug concentration ranges of 1.0 × 10-5 – 1.0 × 10-2, 1.0 × 10-6 – 1.0 × 10-1, 1.0 × 10-7 – 1.0 × 10-2 and 1.0 × 10-8 – 1.0 × 10-2 mol/L with lower detection limits of 5.0 × 10-6, 4.9 × 10-7, 4.8 × 10-8 and 5.0 × 10-9 mol/L for the four mentioned sensors, respectively. The effect of possible interfering species, pharmaceutical additives and some related pharmacological action drugs was investigated using separate solution method. No interference was found. The investigated drug was subjected to forced degradation and the stability indicating of the drug was also studied. The standard addition method was used for determination of the investigated drug in its pharmaceutical dosage forms and biological fluids. The developed sensors gave satisfactory results and these results were validated and statistically analyzed by recoveries studies and compared with those from previously reported methods.